FrogVLE Application in Science Teaching in Secondary Schools in North Malaysia: Teachers’ Perspective - Nofaizah Ramli; Salmiza Saleh (Education Sciences, 2019)
The frogVLE application was launched in Malaysia to provide a virtual learning environment in order to produce competitive and relevant students in the 21st century. As science is one of the most important subjects for the development of a nation, the perspective of teachers as policy implementers should be taken into account in ensuring that the desire is achieved. Hence, this study aimed to investigate the level of application of frogVLE in secondary school science teaching in the northern peninsular of Malaysia. This qualitative study involved 50 secondary school science teachers in Perak, Kedah, Penang and Perlis. Each respondent was required to answer a questionnaire which consists of 20 questions. Five teachers were randomly interviewed by the researcher. The data were analyzed descriptively. The analysis results provide a real picture of how the frogVLE application is used in teaching, as well as the issues, challenges and suggestions for improvements in frogVLE while teaching secondary school science subjects. The findings from this study are expected to help the Ministry of Education to develop programs and improve the use of the frogVLE application in teaching science in secondary schools. In conclusion, a virtual learning environment such as the frogVLE application can only be used optimally to help improve science teaching excellence if the relevant issues are solved and supportis received from all parties.